Severe osteoarticular and skin and soft tissue infection with Mycobacterium bovis following intravesical BCG instillation - Anniek Strijdhorst; L. Charlotte J. de Bree; Reinout van Crevel; Hanna K. de Jong; Sabine M. Hermans (Clinical Infection in Practice, 2024)
We describe the case of a 70-year-old immunocompromised patient who developed a severe disseminated Mycobacterium bovis BCG infection with several infected prosthetic joints and soft tissue abscesses following intravesical BCG instillation for bladder cancer. This case report addresses the risk of severe complications in immunocompromised patients and the challenges in the management of this potentially life-threatening condition.